Effects of prepartum and postpartum bolus injections of trace minerals on performance of beef cows and calves grazing native range - Mundell, L.R.; Stevenson, Jeffrey S.; Grieger, David M.; Pacheco, L.A.; Bolte, J.W.; Aubel, N.A.; Eckerle, G.J.; Macek, M.J.; Havenga, L.J.; Olson, K. C.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Adequate dietary intakes of trace minerals are thought necessary to maximize cow reproduction, calf health, and calf performance. Diets grazed by beef cattle are generally deficient to marginal in copper (Cu), manganese (Mn), selenium (Se), and zinc (Zn) concentrations; therefore, these trace minerals are usually added to the diet in supplement form. The most widely used means of trace-mineral supplementation for grazing cattle is selffed, salt-based, loose mineral supplements. Although cattle do not balance their mineral needs when consuming a self-fed mineral supplement, usually no other practical way of supplying mineral needs exists under grazing conditions. The greatest limitation to using self-fed mineral supplements is variation in animal intake. More direct methods of mineral supplementation include adding minerals to drinking water or feed, oral drenching, ruminal boluses, and injection. Variation in mineral intake is reduced relative to self-fed supplementation, and the additional labor requirement and expense are relatively small. Delivery of supplemental trace minerals using an injectable solution may be a more reliable means of achieving adequate trace-mineral status than using self-fed, salt-based, loose mineral supplements. Bolus injections of trace minerals have been associated with improved average daily gain, feed efficiency, feed intake, or health status of beef calves fed in confinement; however, trace mineral delivery methods of this type have not been fully evaluated with respect to performance of beef cows and suckling calves. The objective of our study was to evaluate the effects of pre- and postpartum bolus injections of a trace mineral solution on beef cow reproductive performance, body weight change, and body condition score change, as well as performance of suckling calves.
Keywords: Beef; Bolus; Trace minerals; Performance